THE CONTRIBUTION OF MARINE GEOLOGY TO THE SOCIO-ECONOMIC DEVELOPMENT OF GREECE: MARINE RESOURCES, INFRASTRUCTURE, ENVIRONMENT SUSTAINABILITY, CULTURAL HERITAGE - Ferentinos, G. (Bulletin of the Geological Society of Greece, 2010)
no abstract available